Expresión gráfica en la enseñanza actual de la arquitectura - Berdillana Rivera, Adrián (2015)
Currently, the college student has internalized the culture of managing digital media and has appropriated technologies in a natural way. New technologies generate transformations in the construction of knowledge and certain “crisis” in traditional models. All this emphasizes the need to conceptualize representation in the learning processes, but also the coexistence of manual and computerized procedures. The first is the bearer of the concepts, while the second is of displays, plots, production and research. Each mode of expression corresponds to a specific role and space.